EMPLEO Y FORMALIDAD. CONCLUSIONES PARA UN COMIENZO - Fernández, José Sergio; Mosquera, Inty Sáez; Domínguez-A., Luis Roberto; Redchuk, Andrés (European Scientific Journal, ESJ, 2015)
Since last decade, theoretical postulates have suggested an alternative approach to informality, from a complementary view. This paper aims to demonstrate theoretically, that employment affects informal activities in an economy, which could lead to the need to consider informality and formality as complementary elements for production. The process followed to achieve the objective was to analyze three scenarios, which included equality and inequality of jobs fraction won and lost. Subsequently mathematical equations were formulated representing scenarios using rate of workers employed, and rate of workers unemployed. Finally the resulting deductions that manifested the phenomenon of informal activities were generated in terms of the effect on employment. The findings show that investment of public spending of transfer to address the informality is inefficient or irrelevant to the increase of production by employment increased, because the informal economy includes informal employment and thus the increase of total production.